Assessment of change in neutrophil-lymphocyte ratio, platelet-lymphocyteratio in patients with acute and chronic urticaria (Annals of Medical Research, 2021)
None
Keywords: Urticaria; Neutrophil-Lymphocyteratio; Platelet-Lymphocyteratio; Systemic Inflammation.